Altruistic behavior in Chinese children with hearing impairment: Associations with power cognition and word comprehension - Weibin Hu; Xueru Zhang; Jiancheng Shao; Yuanfen Wang (Acta Psychologica)
Altruistic behavior is a crucial manifestation in the socialization process of preschool children with hearing impairment, yet research on this topic among Chinese children remains limited. This study investigated the effects of power cognition and word comprehension on altruistic behavior in preschool-aged children with hearing impairment. A sample of 64 children, including both hearing-impaired and typically developing children, completed altruistic behavior tasks, power cognition tasks, word comprehension tasks, and the Raven's Combined Test. The results revealed that: (1) Children with hearing impairment exhibited significantly lower levels of altruistic behavior compared to typically developing children; (2) Both power cognition and word comprehension were positively correlated with altruistic behavior in children with hearing impairment; (3) Word comprehension mediated the relationship between power cognition and altruistic behavior in children with hearing impairment.